Medieval art, architecture and archaeology in Cracow and Lesser Poland - British Archaeological Association.
1 online resource
Keywords: This book explores the medieval art, architecture and archaeology of the city of Cracow and the surrounding region of Lesser Poland. It highlights the role of Cracow and Lesser Poland as a vibrant artistic centre fostering links with Italy, Bohemia, Germany and France.